2016
DOI: 10.1016/j.fertnstert.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone analogues inhibit leiomyoma extracellular matrix despite presence of gonadal hormones

Abstract: This study demonstrates that GnRH-a directly affect the gonadal hormone-regulated collagen-1, fibronectin, and versican production in their presence. These findings suggest that localized therapy with GnRH-a may inhibit leiomyoma growth even in the presence of endogenous gonadal hormone exposure, thereby providing a mechanism to eliminate the hypoestrogenic side effects associated with GnRH-a therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 71 publications
0
14
1
1
Order By: Relevance
“…Interestingly, the relevance of ECM in the growth of UL had been a matter of numerous studies and therapeutical approaches targeting ECM have been proposed repeatedly (e.g. [2225]). Accordingly, future studies should address the possible influence of ECM presented in vitro and of three-dimensional cell cultures on the disappearance of MED12 -mutated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the relevance of ECM in the growth of UL had been a matter of numerous studies and therapeutical approaches targeting ECM have been proposed repeatedly (e.g. [2225]). Accordingly, future studies should address the possible influence of ECM presented in vitro and of three-dimensional cell cultures on the disappearance of MED12 -mutated cells.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, these factors may be of relevance for in vivo growth thus representing possible therapeutic targets. Furthermore, three-dimensional cell cultures [22, 26, 27] may become a model system suitable to replace monolayer cultures if these latter type of culturing turns out better to support the growth of MED12 -mutated cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that the effect of sex hormone levels on patients with different ranges of hysterectomy was not statistically significant. However, after the total hysterectomy, the sex hormone levels were significantly lower than those before surgery [9].…”
Section: Introductionmentioning
confidence: 69%
“…On a molecular level, GnRH agonists decrease the expression of factors important for fibroid growth to include Transforming Growth Factor-Beta, Epidermal Growth Factor, and Insulin-like Growth Factor. Further data from our laboratory has shown reduction of the extracellular components collagen -1, fibronectin, and versican with leuprolide acetate treatment [ 56 , 57 ].…”
Section: Gonadotropin-releasing Hormone Analogsmentioning
confidence: 99%